Communicating Crisis through English-Greek Translation. Issue 6 (2nd November 2019) - Sidiropoulou, Maria
ABSTRACT: The study tackles crisis communication through the press, which reshapes the construction of crisis events, vulnerability, and resilience across English articles and their Greek translations. The strategies involve (a) distinguishing between approaches across English and Greek relative to crisis type, (b) reshaping representations of victims, and (c) assigning responsibility to powerful others. Linguistic variation in re-mediating suffering through translation is of paramount importance, because it may have a de/mobilizing effect on audiences by dis/en-couraging audience response to humanitarian field operators, in crises. The analysis improves understanding of in/efficient intercultural communication in international relief operations. Emerging patterns of managing crisis and hazard representation in original and translated discourses may contribute valuable insights towards better communicating action plans in disaster risk reduction frameworks.